2020
DOI: 10.1002/jts5.76
|View full text |Cite
|
Sign up to set email alerts
|

Victim sensitivity in groups: When is one a detriment to all?

Abstract: Victim sensitivity (VS)—a personality trait reflecting the anxious expectation of being exploited—reliably predicts egoistic behavior in interpersonal situations. Here, we look at intragroup situations and investigate whether even one highly victim‐sensitive individual can have a detrimental effect of solidarity and cooperativeness on the entire group. Two studies—one field study with community residents from Philippine villages who played a solidarity game (N ≈ 800 individuals, 30 villages) and one lab study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 60 publications
2
21
0
Order By: Relevance
“…These considerations can be debated, since personal concerns might be outweighed by concerns about the in-group when individuals strongly identify as group members. Indeed, in-group mistrust has been found to play less of a role among highly identified (compared to less identified) group members (Gollwitzer et al, 2021). Future research can fruitfully address this stimulating question.…”
Section: Potential Specificities Of Victim Sensitivity At the Group Levelmentioning
confidence: 94%
See 1 more Smart Citation
“…These considerations can be debated, since personal concerns might be outweighed by concerns about the in-group when individuals strongly identify as group members. Indeed, in-group mistrust has been found to play less of a role among highly identified (compared to less identified) group members (Gollwitzer et al, 2021). Future research can fruitfully address this stimulating question.…”
Section: Potential Specificities Of Victim Sensitivity At the Group Levelmentioning
confidence: 94%
“…The bulk of the literature on JS has been focused on individual-level processes and interpersonal contexts. Nevertheless, there are several papers in which authors have addressed the relevance of the JS perspectives in political contexts and for grouplevel processes (e.g., Gollwitzer et al, 2021). Here, we selectively review those studies that shed light on the roles that the JS perspectives might play in intergroup contexts.…”
Section: Emerging Evidence For the Relevance Of The Js Perspectives In Intergroup Contextsmentioning
confidence: 99%
“…Turning to intragroup contexts, Gollwitzer et al. (2021) have shown that solidarity and cooperation within a group are reduced by the victim sensitivity of the most victim‐sensitive group member, especially if group‐level risk factors (i.e., external stressors) are present and resilience factors (i.e., social identity) are absent.…”
Section: Introductionmentioning
confidence: 99%
“…Although the two studies reported by Gollwitzer et al. (2021) confirm that one particularly victim‐sensitive member can be detrimental to group outcomes, they leave a number of questions open. First, it is unclear whether VS‐Max specifically affects prosocial behaviours within the group or other group outcomes, too.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation